2016
DOI: 10.3991/ijet.v11i09.6116
|View full text |Cite
|
Sign up to set email alerts
|

Development of Intelligent Teaching System Based on 3D Technology in the Course of Digital Animation Production

Abstract: Abstract-In recent years, with the rapid development of 3D digital technology based on computers and the Internet, human beings have realized visual, 3D observation of the real world. The visual, 3D characteristic of this technology completely conforms to the teaching objective of the digital animation course. Thus, it is profoundly and practically significant to develop an intelligent 3D teaching system and apply it in the course of digital animation production. Through using digital animation production as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…intelligent agents (Li, 2007;Ng et al, 2011). The most general terms used are intelligent e-learning system (Kose & Arslan, 2016), adaptive web-based learning system (Lo, Chan, & Yeh, 2012), or intelligent teaching system (Yuanyuan & Yajuan, 2014). As in ITS, most of the studies either describe the system or include a pilot study but no longer-term results are reported.…”
Section: Assessment and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…intelligent agents (Li, 2007;Ng et al, 2011). The most general terms used are intelligent e-learning system (Kose & Arslan, 2016), adaptive web-based learning system (Lo, Chan, & Yeh, 2012), or intelligent teaching system (Yuanyuan & Yajuan, 2014). As in ITS, most of the studies either describe the system or include a pilot study but no longer-term results are reported.…”
Section: Assessment and Evaluationmentioning
confidence: 99%
“…Teaching course content The disciplines that are taught through adaptive systems are diverse, including environmental education (Huang, 2018), animation design (Yuanyuan & Yajuan, 2014), language learning (Jia, 2009;Vlugter et al, 2009), Computer Science (Iglesias, Martinez, Aler, & Fernandez, 2009) and Biology (Chaudhri et al, 2013). Walsh, Tamjidul, and Williams (2017), however, present an adaptive system based on machine learning-human machine learning symbiosis from a descriptive perspective, without specifying any discipline.…”
Section: Assessment and Evaluationmentioning
confidence: 99%
“…The creation of a three-dimensional mesh is what Modeling refers to, regardless of whether the end product is a bug-eyed extraterrestrial or a teacup. The steps you take to complete that model are primarily determined by the strategies that make the most intuitive sense to you as an individual (Ji & Liu, 2016).…”
Section: Different Varieties Of 3d Artworkmentioning
confidence: 99%
“…Reason for this is traditional teaching methods are still used for 3D animation production course which is a discipline keeping pace with the times and having strong practical property. But using previous old teaching software has seriously restricted and prevented teaching quality improvement [3]. Detailed manifestations are: (1) Teaching method is still conservative.…”
Section: Introductionmentioning
confidence: 99%